Management of 760-g Extremely Premature Infant With Dextro-Transposition of the Great Arteries. Issue 4 (July 2020) - Khazaal, Jawad R.; Sowinski, Heather A.; Ratnasamy, Christopher; Vettukattil, Joseph J.; Haw, Marcus P.
Extremely low birth weight neonates with complex congenital heart disease have increased mortality risk. Multi-organ dysfunction, pulmonary disease, fluctuating pulmonary vascular resistance, and complex cardiovascular anatomy create a challenge for effective management. We present the case of a 760-g neonate with dextro-transposition of the great arteries, ventricular septal defect, patent ductus arteriosus, and single coronary artery with proximal intramural segment of the right coronary artery branch. We describe features of preoperative care, surgical intervention, and postoperative course that enabled this infant to survive.